2017
DOI: 10.1097/md.0000000000008455
|View full text |Cite
|
Sign up to set email alerts
|

“Message from a turtle”

Abstract: Rationale:Salmonella enterica subsp arizonae is a common gut inhabitant of reptiles (snakes are the most common reservoir, but it also occurs in turtles). Alhough human cases owing to this organism are exceedingly rare, it may occasionally infect young infants and immunocompromised individuals with a history of intimate associations with reptiles. Our case is the 20th one among the infections with S arizonae in children, but the 2nd one of otitis and the first of mastoiditis. The other cases had different anat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…may be high particularly regarding treatment, as human infections due to S. enterica subsp. arizonae can occur and have been described before ( Gavrilovici et al, 2017 ; Lakew et al, 2013 ).…”
Section: Discussionmentioning
confidence: 86%
“…may be high particularly regarding treatment, as human infections due to S. enterica subsp. arizonae can occur and have been described before ( Gavrilovici et al, 2017 ; Lakew et al, 2013 ).…”
Section: Discussionmentioning
confidence: 86%
“…However, more research is needed to properly determine the differences between the intestinal microbiota of exotic and domestic European species of reptiles. A number of publications have shown that RAS/REPAS could lead to serious infections, which can end up with septicemia, miscarriage or death [ 3 , 4 , 15 19 ]. That is why European reptiles should be screened.…”
Section: Introductionmentioning
confidence: 99%
“…Considering reports from last 6 years and published by European scientists, reptile-associated salmonellosis with detection of the same Salmonella serovar in both patient's blood and reptile faeces was observed in Switzerland -2016 (years of publication) [90], UK (UK) -2015 [91], Romania -2017 [92], France -2015 [88,93] and Spain -2015 [88,89]. In Switzerland, the first case of reptile-associated sinusitis due to S. enterica subsp.…”
Section: Cases Of Reptile-associated Salmonellosis In Humansmentioning
confidence: 99%